2015
DOI: 10.1371/journal.pone.0128096
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Induced Keratinization Processes in an Immortalized Human Meibomian Gland Epithelial Cell Line

Abstract: PurposeThe aim of this study was to evaluate a human meibomian gland epithelial cell line (HMGEC) as a model for meibomian gland (patho)physiology in vitro.MethodsHMGEC were cultured in the absence or presence of serum. Sudan III lipid staining, ultrastructural analysis and lipidomic analyses were performed. Impedance sensing, desmoplakin 1/2 mRNA and cytokeratin (CK) 1, 5, 6, 14 levels were evaluated. Serum containing medium supplemented with higher serum, glucose, an omega-3 lipid cocktail, eicosapentaenoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
(51 reference statements)
1
34
1
Order By: Relevance
“…One day after medium exchange was selected based on previous investigations with 2D-cultured HMGECs. 15 In that study, lipid production in HMGECs reached a maximum 1 day after switching to differentiation medium and gradually declined thereafter. Histologic examination revealed that 1-day culture with differentiation medium promoted the apical FIGURE 2.…”
Section: Membrane-based 3d Cell Culturementioning
confidence: 76%
See 4 more Smart Citations
“…One day after medium exchange was selected based on previous investigations with 2D-cultured HMGECs. 15 In that study, lipid production in HMGECs reached a maximum 1 day after switching to differentiation medium and gradually declined thereafter. Histologic examination revealed that 1-day culture with differentiation medium promoted the apical FIGURE 2.…”
Section: Membrane-based 3d Cell Culturementioning
confidence: 76%
“…This finding intrigued us as recently it was shown that maturing meibocytes are connected by desmosomes and HMGECs increase cell contacts when treated with serum. 15,33 Apparently, the basally located HMGECs in direct contact with the membranes were unable to develop strong contact points comparable to desmosomes or hemidesmosomes. Interestingly, in sebocytes, extracellular matrix precoating was not necessary to form a stable multilayer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations